Positive electrode active material and preparation method and application thereof

By preparing a positive electrode active material with solid solution core and carbon coating of lithium manganese iron phosphate and lithium manganese oxide, the problems of low ion transport capability and compaction density of LMFP materials are solved, and the electrochemical performance and energy density of lithium-ion batteries are significantly improved.

CN119695097APending Publication Date: 2025-03-25NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411783194.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The ion transport capability of lithium manganese iron phosphate (LMFP) cathode material has poor ion transport capability and low powder compaction density, which affects the electrochemical performance and energy density of lithium-ion batteries.

Method used

By preparing a positive electrode active material including secondary particles composed of primary particles, the primary particles contain a core and a carbon coating layer, the core is a solid solution formed by lithium manganese iron phosphate and lithium manganese oxide, and the particle size distribution of the primary particles is controlled to improve the electronic conductivity and ion transport capability of the material.

Benefits of technology

The circulation performance, first-time Coulomb efficiency and energy density of lithium-ion batteries have been significantly improved, and the balanced improvement of compaction density and electrochemical performance has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695097A_ABST
    Figure CN119695097A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material as well as a preparation method and application thereof. The positive electrode active material comprises secondary particles consisting of primary particles, each primary particle comprises an inner core and a carbon coating layer arranged on at least part of the surface of the inner core; the inner core comprises a solid solution formed by lithium iron manganese phosphate and lithium manganate; the primary particles comprise primary particles A and primary particles B, the particle size of the primary particles A is 50-200nm, and the median particle size D50 is 80-120nm; the particle size of the primary particles B is 400-800 nm, and the median particle size D50 is 500-600 nm. The positive electrode active material has relatively high powder compaction density and ion transmission capability, and the electrochemical performance and energy density of the lithium ion battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a positive electrode active material, in particular to a positive electrode active material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage, wide operating temperature range, low self-discharge rate, no memory effect, and environmental protection and low carbon, and are widely used in various fields, such as portable electronic devices, electric vehicles, aerospace, renewable energy storage, etc. As one of the key components of lithium-ion batteries, positive electrode active materials play a core role in improving the electrochemical performance of lithium-ion batteries.

[0003] As an important cathode material for lithium-ion batteries, lithium manganese iron phosphate (LMFP) has attracted widespread attention due to its high safety, good cycle stability and cost advantages. However, LMFP has poor ion transmission capacity and low powder compaction density, which has a great impact on the electrochemical performance and energy density of the battery. Although existing technologies have made breakthroughs in improving the performance of lithium manganese iron phosphate cathode materials, it is still difficult to achieve a balanced improvement in compaction density and electrochemical performance.

[0004] Therefore, how to improve the compaction density of LMFP while ensuring excellent electrochemical performance is a hot topic in current research. Summary of the invention

[0005] In view of the above-mentioned defects, the present invention provides a positive electrode active material, which has both high powder compaction density and ion transmission capacity, and can effectively improve the electrochemical performance and energy density of lithium-ion batteries.

[0006] The present invention also provides a method for preparing the above-mentioned positive electrode active material. The positive electrode active material prepared by the preparation method has a high ion transmission capacity and can also achieve a high powder compaction density, which can effectively improve the electrochemical performance and energy density of lithium-ion batteries.

[0007] The present invention also provides a positive electrode sheet, which includes the above-mentioned positive electrode active material, or the positive electrode active material prepared by the above-mentioned preparation method. Therefore, the positive electrode sheet is used in a lithium-ion battery to enable the battery to have higher electrochemical performance and energy density.

[0008] The present invention also provides a lithium-ion battery, which comprises the above-mentioned positive electrode active material, or the positive electrode active material prepared by the above-mentioned preparation method, or the above-mentioned positive electrode sheet, so that the battery has higher electrochemical performance and energy density.

[0009] A first aspect of the present invention provides a positive electrode active material, the positive electrode active material comprising secondary particles composed of primary particles; the primary particles comprising an inner core and a carbon coating layer disposed on at least a portion of the surface of the inner core; the inner core comprising a solid solution formed by lithium manganese iron phosphate and lithium manganate;

[0010] The primary particles include primary particles A and primary particles B. The particle size of the primary particles A is 50 to 200 nm, and the median particle size D50 is 80 to 120 nm. The particle size of the primary particles B is 400 to 800 nm, and the median particle size D50 is 500 to 600 nm.

[0011] The positive electrode active material as described above, wherein the mass content m of the lithium manganate in the positive electrode active material satisfies 0<m≤3%;

[0012] And / or, the mass content z of the carbon coating layer in the positive electrode active material satisfies 0<z≤3%.

[0013] The positive electrode active material as described above, wherein the ratio of the number of the primary particles A to the number of the primary particles B is 2:8 to 8:2;

[0014] and / or, the porosity of the secondary particles is 5 to 25%;

[0015] And / or, the particle size distribution dispersion of the primary particles is 1.67 to 2.86.

[0016] The positive electrode active material as described above, wherein the powder compaction density of the positive electrode active material is 2.26 to 2.46 g / cm 3 .

[0017] The positive electrode active material as described above, wherein the positive electrode active material further comprises a doping element;

[0018] The doping element includes at least one of Al, Mg, Ni, Co, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y;

[0019] Preferably, the mass content of the doping element in the positive electrode active material is 500 to 5000 ppm.

[0020] The positive electrode active material as described above, wherein the chemical composition of the solid solution satisfies Formula 1,

[0021] Li 1+b Fe 1-x-y Mn x D y PO4·LiMn2O4 Formula 1

[0022] In Formula 1, -0.01≤b≤0.04, 0.2≤x≤0.8, 0.0005≤y≤0.005, and D is the doping element.

[0023] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:

[0024] Mixing MnO2 and a manganese-containing compound with a complexing agent in a molar ratio of (0.2-0.8): (0.8-0.2), reacting at 80-100° C. for 1-3 hours to obtain a gel product; sintering the gel product at 700-900° C. for 3-8 hours in an inert atmosphere to obtain a composite manganese source;

[0025] The raw material system including the lithium source, the composite manganese source, the iron source, the phosphorus source and the carbon source is sequentially subjected to sand milling and spray drying to obtain a precursor material; the precursor material is heat-sintered at 650-700° C. for 6-10 hours to obtain the positive electrode active material.

[0026] The method for preparing the positive electrode active material as described above, wherein the median particle size D50 of the composite manganese source is 4 to 9 μm, and / or the tap density is 2.50 to 3.80 g / cm 2 , and / or, specific surface area of ​​0.30 to 0.70 m 2 / g.

[0027] A third aspect of the present invention provides a positive electrode sheet, which includes the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect.

[0028] A fourth aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect.

[0029] The positive electrode active material in the present invention includes secondary particles composed of primary particles. By making the primary particles include a core and a carbon coating layer disposed on at least a portion of the surface of the core, and the core includes a solid solution formed by lithium iron manganese phosphate and lithium manganate, the electronic conductivity and ion transmission capacity of the positive electrode active material can be effectively improved, thereby improving the cycle performance and the first coulomb efficiency of the battery. At the same time, controlling the particle size distribution of the primary particles A and the primary particles B in the primary particles so that they are within the above range helps the primary particles to form a gradation relationship, which can not only effectively improve the powder compaction density of the positive electrode active material, but also form a higher packing density, reduce the porosity of the secondary particles, thereby effectively improving the capacity and energy density of the battery. Therefore, the positive electrode active material in the present invention can comprehensively improve the electrochemical performance and energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the composite manganese source prepared in Example 1 of the present invention;

[0031] Figure 2 This is a SEM image of the positive electrode active material prepared in Example 1 of the present invention;

[0032] Figure 3 This is the XRD diagram of the positive electrode active material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] As an important positive electrode active material, lithium manganese iron phosphate (LMFP) has the advantages of excellent low-temperature performance, high energy density and voltage platform. However, since the LMFP material has a hexagonal close-packed structure, the FeO6 and MnO6 are located on the octahedron and are cross-connected by PO4 tetrahedrons, and it is impossible to form a continuous FeO6 (MnO6) octahedral network, so its conductivity is very poor. At the same time, this structure will also cause lithium ions to diffuse only along one-dimensional channels during charging and discharging, which will greatly hinder the migration of lithium ions and affect the ion diffusion capacity of the material. In addition, this crystal structure will also make it difficult for primary particles to be closely stacked, and it is difficult to achieve a high compaction density during the compaction process.

[0035] The inventor creatively discovered that by making the primary particles in the positive electrode active material include a core and a carbon coating layer, wherein the core includes a solid solution formed by lithium manganese iron phosphate and lithium manganate, the conductivity and ion diffusion capacity of the material can be effectively improved. At the same time, by controlling the particle size distribution of the primary particles to be within a specific range, a gradation can be formed between the primary particles, effectively improving their stacking density, thereby improving the compaction density of the material.

[0036] Based on the above analysis, the first aspect of the present invention provides a positive electrode active material, which includes secondary particles composed of primary particles; the primary particles include an inner core and a carbon coating layer disposed on at least a portion of the surface of the inner core; the inner core includes a solid solution formed by lithium manganese iron phosphate and lithium manganate;

[0037] The primary particles include primary particles A and primary particles B. The particle size of the primary particles A is 50 to 200 nm, and the median particle size D50 is 80 to 120 nm. The particle size of the primary particles B is 400 to 800 nm, and the median particle size D50 is 500 to 600 nm.

[0038] The positive electrode active material in the present invention can effectively improve the electrochemical performance and energy density of the battery. After analysis, the inventor believes that the main reasons are:

[0039] The lithium manganese oxide in the solid solution has a spinel crystal structure. This crystal structure has three lithium ion transmission channels. Doping it in lithium iron manganese phosphate can provide a new reaction path and reduce the energy barrier of the original reaction path, thereby effectively reducing the activation energy of lithium ions in the insertion and deinsertion reactions, making charging and discharging easier and improving the ion diffusion capacity of the material; at the same time, by coating the surface of the primary particles with a carbon coating layer, the positive electrode active material can have a higher conductivity, thereby comprehensively improving the first coulombic efficiency cycle performance of the battery.

[0040] Moreover, the charge and discharge process is often accompanied by the deintercalation and phase transition of lithium ions, which will lead to incomplete or uneven phase transition inside the material during long-term cycling, forming a disordered phase structure and causing material performance to deteriorate. However, since this solid solution can improve the diffusion of lithium ions and increase the diffusion rate, it can also reduce the adverse phase transition caused by the deintercalation and deintercalation of lithium ions, which helps to improve the battery's cycle performance.

[0041] In addition, by making the primary particles include primary particles A and primary particles B of different particle sizes, and controlling the particle sizes and D50 of primary particles A and primary particles B to be within the above-mentioned range, a gradation relationship can be formed between the primary particles, that is, primary particles with smaller particle sizes are filled in the gaps between primary particles with larger particle sizes, achieving a higher packing density, thereby effectively improving its powder compaction density and improving the capacity and energy density of the battery.

[0042] The "particle size" in the present invention refers to the particle size range of the particles, that is, the range formed by the minimum and maximum particle sizes.

[0043] The "D50" in the present invention refers to the median particle size of the particles, that is, the particle size corresponding to when the cumulative particle size distribution percentage of the particles reaches 50%.

[0044] The "particle size" and "D50" in the present invention can be obtained by performing SEM testing on the positive electrode active material and using professional particle size analysis software Nano Measurer to calibrate and count the size of the primary particles in the SEM image.

[0045] Exemplarily, the particle size of primary particle A is 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm; D50 is 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm or 120nm.

[0046] Illustratively, the particle size of primary particle B is 400nm, 440nm, 480nm, 820nm, 560nm, 600nm, 640nm, 680nm, 720nm, 760nm or 800nm; D50 is 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, 600nm.

[0047] Furthermore, the mass content of lithium manganese oxide or carbon coating in the positive electrode active material can be controlled to make the lithium-ion battery have higher electrochemical performance.

[0048] Among them, the mass content of lithium manganese oxide in the positive electrode active material will affect the electrochemical properties of the material. Too high a content will cause serious lattice distortion in the material, seriously affecting the electrical properties of the material; too low a content will lead to an inability to fully play its role and insufficient improvement in the lithium ion diffusion capacity.

[0049] The mass content of the carbon coating in the positive electrode active material will directly affect the conductivity of the material, and also have a certain impact on the battery energy density. Since carbon is an inactive substance in electrochemical reactions, the content of the carbon coating should not be too much, otherwise it will reduce the battery energy density; at the same time, if the content of the carbon coating is too little, it will not form a sufficient conductive network, affecting the conductivity of the material.

[0050] In a specific embodiment, the mass content m of lithium manganese oxide in the positive electrode active material satisfies 0<m≤3%. Within this range, the first coulombic efficiency and cycle performance of the battery can be further improved. Specifically, during the preparation process, the mass content of lithium manganese oxide in the positive electrode active material can be controlled by controlling the sintering conditions of the precursor material.

[0051] Illustratively, m is 0.01%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.

[0052] The “mass content of lithium manganate in the positive electrode active material” in the present invention can be obtained by testing using a common method used by those skilled in the art, for example, by XRD testing.

[0053] In a specific embodiment, the mass content z of the carbon coating layer in the positive electrode active material satisfies 0<z≤3%. In this range, not only can the loss of energy density be reduced, but also a sufficient conductive network can be formed, so that the lithium-ion battery has higher first coulomb efficiency performance and energy density.

[0054] Illustratively, z is 0.01%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.

[0055] The “mass content of the carbon coating layer in the positive electrode active material” in the present invention can be obtained by testing using a common method used by those skilled in the art, for example, by testing with a carbon-sulfur analyzer.

[0056] Furthermore, the ratio of the number of primary particles A to primary particles B, or the discreteness of the particle size distribution, can be adjusted to reduce the porosity of the secondary particles, thereby achieving a higher packing density, further improving the powder compaction density of the material, and making the lithium-ion battery have a higher capacity and energy density.

[0057] Specifically, during the preparation process, the ratio of the number of primary particles A and primary particles B, or the dispersion of the particle size distribution can be further controlled by controlling the preparation conditions of the composite manganese source (such as sintering conditions, selection of manganese-containing compounds) or the sintering conditions of the precursor material.

[0058] In a specific embodiment, the ratio of the number of primary particles A to primary particles B is 2:8 to 8:2. Within this range, it is helpful to improve the packing density of the primary particles, so that the small-sized primary particles can be better filled in the gaps of the large-sized primary particles, achieving a higher compaction density, and making the battery have a higher capacity and energy density.

[0059] Illustratively, the ratio of the number of primary particles A to primary particles B is 2:8, 3:7, 4:6, 5:5, 6:4, 7:3 or 8:2.

[0060] The test method of "the ratio of the number of primary particles A to primary particles B" in the present invention can be consistent with the test methods of "particle size" and "D50" mentioned above, and will not be described in detail here.

[0061] In a specific embodiment, the particle size distribution dispersion of the primary particles is 1.67 to 2.86. Within this range, the primary particle size is relatively suitable, so that the primary particles can be better stacked, effectively improving the powder compaction density of the material and improving the energy density of the battery.

[0062] The "particle size distribution dispersion" in the present invention is obtained by performing SEM testing on primary particles and using professional particle size analysis software to calibrate and count the size of the primary particles in the SEM image to obtain D10, D50 and D90, which are calculated according to (D90-D10) / D50.

[0063] Among them, D10 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the particles reaches 10%, and D90 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the particles reaches 90%.

[0064] Illustratively, the particle size distribution dispersion of the primary particles is 1.67, 1.87, 2.07, 2.27, 2.47, 2.67 or 2.86.

[0065] Preferably, the D10 of the primary particles is 55 to 110 nm, the D50 is 255 to 410 nm, and the D90 is 785 to 795 nm.

[0066] In a specific embodiment, the porosity of the secondary particles is 5-25%. Within this range, the porosity of the secondary particles is relatively suitable, which can not only provide more channels for lithium ion diffusion, effectively improve the battery capacity, but also will not affect the infiltration of electrolyte and ion transmission due to too low porosity, avoiding adverse effects on the battery cycle.

[0067] Illustratively, the porosity of the secondary particles is 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23% or 25%.

[0068] The "porosity" in the present invention can be obtained by testing using methods commonly used by those skilled in the art. For example, the gas adsorption method (BET method) can be used to measure the gas adsorption amount of the positive electrode material under different pressures and calculate the porosity.

[0069] In one embodiment, the powder compaction density of the positive electrode active material is 2.26 to 2.46 g / cm 3 Within this range, not only can the high energy density of the battery be guaranteed, but also the contact area between active materials will not be too small due to the high compaction density, thus affecting the battery capacity.

[0070] Exemplarily, the powder compaction density is 2.26 g / cm 3 , 2.28g / cm 3 , 2.30g / cm 3 , 2.32g / cm 3 , 2.34g / cm 3 , 2.36g / cm 3 , 2.38g / cm 3 , 2.40g / cm3 , 2.42g / cm 3 , 2.44g / cm 3 or 2.46 g / cm 3 .

[0071] The "powder compaction density" in the present invention is obtained by testing with a powder compaction density tester, with a test pressure of 220 MPa and a pressure holding time of 15 s.

[0072] Furthermore, the positive electrode active material can be doped to improve the charge and discharge performance and cycle performance of the material.

[0073] In a specific embodiment, the positive electrode active material further includes a doping element;

[0074] The doping elements include at least one of Al, Mg, Ni, Co, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y.

[0075] By doping the positive electrode active material with at least one of the above elements, the Li-O bond can be extended, the interstitial position in the octahedral LiO6 can be increased, and the structure of olivine can be stabilized during the lithium insertion and extraction process, thereby realizing the Li + Rapid transmission improves the battery's cycle performance and first coulombic efficiency.

[0076] When the positive electrode active material includes multiple elements of the above elements at the same time, the present invention does not specifically limit the ratio between the elements.

[0077] At the same time, the mass content of doping elements in the positive electrode active material can also be controlled to further improve the electrochemical performance of the material. Too much doping elements will cause them to occupy the position of lithium ions in the crystal structure, destroy the crystal structure of the material, hinder the diffusion of lithium ions, and reduce the electrochemical performance of the material; too low content will result in the inability to effectively improve the crystal structure of the material, and the improvement of the lithium ion diffusion rate is very limited.

[0078] In a specific embodiment, the mass content of the doping element in the positive electrode active material is 500-5000 ppm. Within this range, the content of the doping element is relatively appropriate, which can effectively improve the lithium ion diffusion capacity of the material, thereby further improving the first coulombic efficiency of the battery.

[0079] Illustratively, the mass content of the doping element in the positive electrode active material is 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm or 5000 ppm.

[0080] In one embodiment, the chemical composition of the solid solution satisfies Formula 1,

[0081] Li 1+b Fe 1-x-y Mn x D y PO4·LiMn2O4 Formula 1

[0082] In Formula 1, -0.01≤b≤0.04, 0.2≤x≤0.8, 0≤y≤0.05, and D is a doping element.

[0083] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:

[0084] Mix MnO2 and a manganese-containing compound with a complexing agent in a molar ratio of (0.2-0.8): (0.8-0.2), react at 80-100°C for 1-3 hours to obtain a gel product; sinter the gel product at 700-900°C for 3-8 hours in an inert atmosphere to obtain a composite manganese source;

[0085] The raw material system including lithium source, composite manganese source, iron source, phosphorus source and carbon source is sequentially subjected to sand milling and spray drying to obtain a precursor material; the precursor material is heat-sintered at 650-700° C. for 6-10 hours to obtain a positive electrode active material.

[0086] Specifically, MnO2 and a manganese-containing compound are mixed in a molar ratio of (0.2-0.8): (0.8-0.2), and then a complexing agent is added, and the mixture is reacted at 80-100°C for 1-3 hours to obtain a gel product; the gel product is sintered under the protection of an inert atmosphere at a sintering temperature of 700-900°C and a holding time of 3-8 hours to obtain a composite manganese source.

[0087] The raw material system including the above-mentioned composite manganese source, lithium source, iron source, phosphorus source and carbon source is mixed, and then successively subjected to sand milling and spray drying to obtain a precursor material; the precursor material is sintered under the protection of an inert atmosphere at a sintering temperature of 650 to 700° C. and a heat preservation time of 6 to 10 hours to obtain a positive electrode active material.

[0088] It is understood that the sol-gel reaction in the preparation process of the gel product also requires the participation of a solvent. The present invention does not specifically limit the type of solvent, and a suitable solvent, such as deionized water, can be selected according to actual conditions.

[0089] Illustratively, the molar ratio of MnO2 to the manganese-containing compound is 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3 or 0.8:0.2.

[0090] Illustratively, during the preparation of the composite manganese source, the reaction temperature is 80°C, 85°C, 90°C, 95°C or 100°C; and the reaction time is 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0091] Illustratively, during the preparation of the composite manganese source, the sintering temperature is 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C or 900°C, and the holding time is 3h, 4h, 5h, 6h, 7h or 8h.

[0092] Illustratively, during the sintering of the precursor material, the sintering temperature is 650°C, 655°C, 660°C, 665°C, 670°C, 675°C, 680°C, 685°C, 690°C, 695°C or 700°C, and the holding time is 6h, 7h, 8h, 9h or 10h.

[0093] The present invention does not specifically limit the amount of the complexing agent to be added, and a suitable amount can be selected according to actual conditions. Preferably, the amount of the complexing agent added is 20-50% of the theoretical mass of the composite manganese source.

[0094] The calculation method of the "theoretical generation mass of the composite manganese source" in the present invention is as follows:

[0095] The theoretical generated mass of 1 mol of composite manganese source (g) = a×N1+(1-a)×N2, where a is 0.2~0.8; N1 is the molar mass of MnO2, and N2 is the molar mass of the manganese-containing compound, and the unit is g / mol.

[0096] The "manganese-containing compound" in the present invention refers to a compound containing manganese element, and is different from MnO2. Exemplarily, the manganese-containing compound includes at least one of manganese monoxide, manganese trioxide, manganese tetraoxide, manganese pentoxide, manganese carbonate, manganese oxalate, manganese sulfate, manganese phosphate, manganese dihydrogen phosphate, manganese hydroxide, manganese nitrate, manganese chloride, manganese sulfide, and manganese acetate.

[0097] The present invention does not specifically limit the type of complexing agent, and illustratively includes at least one of citric acid, ammonium citrate, maleic acid, oxalic acid, ammonium oxalate, ascorbic acid, ethanolamine, diethanolamine, and triethanolamine.

[0098] The present invention does not specifically limit the sources of MnO2, manganese-containing compounds and complexing agents, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.

[0099] The present invention does not specifically limit the heating rate during sintering in the preparation process of the composite manganese source. For example, the heating rate is 3 to 5° C. / min.

[0100] The lithium source in the present invention refers to a raw material that provides lithium elements, the iron source refers to a raw material that provides iron elements, the phosphorus source refers to a raw material that provides phosphorus elements, and the carbon source refers to a raw material that provides carbon elements. As long as the target element (Li, Fe, P, C) is contained, it belongs to the definition of the present invention. It should be noted that when the raw material includes two or more elements of the target element at the same time, the raw material can be understood as an element source of two target elements. For example, when the raw material is iron phosphate, it acts as a phosphorus source and an iron source at the same time; when the raw material is lithium dihydrogen phosphate, it acts as a lithium source and a phosphorus source at the same time.

[0101] Exemplarily, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium dihydrogen phosphate, and lithium oxalate; the iron source includes at least one of ferric phosphate, ferric nitrate, ferric oxide, ferric nitrate, and ferric oxalate; the phosphorus source includes at least one of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, ammonium phosphate, and ammonium monohydrogen phosphate; and the carbon source includes at least one of glucose, sucrose, starch, polyvinyl alcohol, polyethylene glycol, citric acid, and ascorbic acid.

[0102] The present invention does not specifically limit the sources of the lithium source, iron source, phosphorus source and carbon source, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.

[0103] The present invention does not specifically limit the molar ratio of the composite manganese source, lithium source, iron source and phosphorus source. Further, the chemical composition of lithium iron manganese phosphate in the solid solution can be controlled to satisfy Formula 1 by controlling the molar ratio of Li, Mn, Fe and P to (0.99-1.04): (0.2-0.8): (0.8-0.2): 1.0.

[0104] The present invention does not specifically limit the amount of carbon source added. Furthermore, the mass content of the carbon coating layer in the positive electrode active material can be controlled by controlling the amount of carbon source added or the sintering conditions. Exemplarily, when the amount of carbon source added accounts for 8-12% of the theoretical mass of lithium manganese iron phosphate, it helps to make the mass content z of the carbon coating layer in the positive electrode active material satisfy 0<z≤3%.

[0105] The calculation method of the "theoretical generated mass of lithium manganese iron phosphate" in the present invention is as follows:

[0106] According to the chemical formula: Li 1+b Fe 1-x Mn x PO4 lithium manganese iron phosphate, the theoretical generated mass of 1 mol lithium manganese iron phosphate (g) = (1 + b) × M1 + (1-x) × M2 + x × M3 + M4 + 4 × M5, where M1 is the molar mass of Li, M2 is the molar mass of Fe, M3 is the molar mass of Mn, M4 is the molar mass of P, and M5 is the molar mass of O, and the unit is g / mol.

[0107] The present invention does not specifically limit the conditions for sand milling, and sand milling can be performed using a common method used by those skilled in the art. For example, the rotation speed is 1500 to 2400 r / min, the time is 15 to 60 min, and the solid content of the slurry after sand milling is 20 to 35%.

[0108] The present invention does not specifically limit the conditions for spray drying, and the spray drying can be carried out by a common method used by those skilled in the art. For example, the air inlet temperature is 220-280°C, and the air outlet temperature is 90-110°C.

[0109] The present invention does not specifically limit the heating rate during the sintering process of the precursor material. Exemplarily, the heating rate is 3 to 7° C. / min.

[0110] Furthermore, in the preparation of the precursor material, the raw material system may also include a dopant, and the doping element in the dopant includes at least one of Al, Mg, Ni, Co, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y.

[0111] Furthermore, the amount of dopant added can be controlled, thereby controlling the mass content of the doping element in the positive electrode active material. For example, when the mass of the doping element in the dopant accounts for 0.05-0.5% of the theoretical mass of lithium manganese iron phosphate, it helps to make the mass content of the doping element in the positive electrode active material between 500 and 5000 ppm.

[0112] The preparation method of the present invention first uses a specific molar ratio of MnO2 and a manganese-containing compound to prepare a composite manganese source, wherein the composite manganese source includes at least two manganese compounds, and different manganese compounds have different nucleation conditions, such as nucleation temperature and insulation time; therefore, when the composite manganese source is used as a raw material in the preparation process of lithium manganese iron phosphate, primary particles of different particle sizes will be generated at the same sintering temperature and insulation time, which is helpful to obtain primary particles with a specific particle size distribution at the specific molar ratio, i.e., primary particles A and primary particles B, thereby effectively improving the compaction density of the positive electrode active material and enhancing the capacity and energy density of the battery. At the same time, in the process of generating lithium iron manganese phosphate, MnO2 in the composite manganese source will compete with lithium iron manganese phosphate for Li to generate lithium manganese oxide, and then generate a solid solution formed by lithium iron manganese phosphate and lithium manganese oxide; and the lithium manganese oxide in the solid solution has a spinel crystal structure, which can provide a new reaction path and reduce the energy barrier of the original reaction path, thereby effectively reducing the activation energy of lithium ions in the insertion and deinsertion reactions, making charging and discharging easier and improving the ion diffusion capacity of the positive electrode active material; in addition, the addition of the carbon source helps to form a carbon coating layer on the surface of the primary particles, giving the positive electrode active material a higher conductivity, thereby comprehensively improving the battery's cycle performance and first coulombic efficiency.

[0113] Furthermore, the structure of the composite manganese source, such as the median particle size D50, tap density and specific surface area, also has a certain influence on the specific surface area and compaction density of the positive electrode active material, which in turn affects the electrochemical properties of the battery, such as the first coulombic efficiency, cycle performance, and energy density.

[0114] Among them, if D50 is too small, the specific surface area of ​​the positive electrode active material will be larger. Although it can improve the electrochemical activity of the material, it will also cause the material to agglomerate and affect its electronic conductivity. If D50 is too large, it will increase the compaction density of the material to a certain extent, but it is not conducive to the transmission of lithium ions, resulting in a decrease in electrochemical performance.

[0115] A tap density that is too high will increase the volume energy density of the battery to a certain extent, but overly tight filling of the material will increase the stress inside the material, causing cracks during the cycle and affecting the cycle stability; a tap density that is too low means that there will be less active material in the same volume, resulting in a decrease in energy density.

[0116] A larger specific surface area usually means more active sites during the material synthesis process, which can speed up the electrochemical reaction rate and improve the electrochemical activity; a smaller specific surface area is more likely to form a higher compaction density, but the active sites are reduced and the overall electrochemical activity of the material will decrease.

[0117] In a specific embodiment, the median particle size D50 of the composite manganese source is 4 to 9 μm. Within this range, the particle size of the composite manganese source is relatively suitable, which can not only make the positive electrode active material have a higher specific surface area, but also prevent agglomeration, which is beneficial to improving the lithium ion transport performance and electronic conductivity of the material; at the same time, it can also achieve a higher compaction density and improve the energy density of the material.

[0118] Illustratively, D50 is 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or 9 μm.

[0119] In one specific embodiment, the tap density of the composite manganese source is 2.50 to 3.80 g / cm 2 Within this range, a higher volumetric energy density can be achieved without affecting the battery's cycle performance.

[0120] For example, the tap density is 2.50 g / cm 2 , 2.60g / cm 2 , 2.80g / cm 2 、3.00g / cm 2 、3.20g / cm 2 , 3.40g / cm 2 、3.60g / cm 2 or 3.80g / cm 2 .

[0121] In one embodiment, the specific surface area of ​​the composite manganese source is 0.30 to 0.70 m 2 / g. Within this range, the electrochemical performance of the positive electrode active material can be effectively improved.

[0122] For example, the specific surface area is 0.30 m 2 / g, 0.35m 2 / g, 0.40m 2 / g, 0.45m 2 / g, 0.50m 2 / g, 0.55m 2 / g, 0.60m 2 / g, 0.65m 2 / g or 0.70m 2 / g.

[0123] The third aspect of the present invention provides a positive electrode sheet, which includes the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect. Therefore, the positive electrode sheet is used in a lithium-ion battery to effectively improve the first coulombic efficiency, cycle performance, capacity and energy density of the battery.

[0124] The present invention does not specifically limit the composition and structure of the positive electrode sheet. In one embodiment, the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode collector, and the positive electrode active material layer includes the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect.

[0125] The present invention does not specifically limit the type of positive electrode current collector, which can be selected conventionally in the art, for example, aluminum foil.

[0126] The present invention does not specifically limit the preparation method of the positive electrode sheet, and the positive electrode sheet can be prepared by a common method used by those skilled in the art.

[0127] It can be understood that the positive electrode active material layer also includes a binder and a conductive agent. The present invention does not specifically limit the specific types of the binder and the conductive agent, which can be selected conventionally in the art. For example, the binder can be selected from at least one of polyvinylidene fluoride (PVDF), lithium polyacrylate (LiPAA), polyacrylic acid (PAA), polyvinyl alcohol (PVA), and polyacrylamide (PAM); the conductive agent can be selected from at least one of acetylene black, Ketjen black, graphite, carbon nanotubes, and graphene.

[0128] A fourth aspect of the present invention provides a lithium ion battery, which includes the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect.

[0129] The present invention does not specifically limit the assembly method of the lithium-ion battery, and the assembly can be performed in a conventional manner in the art.

[0130] The lithium ion battery in the present invention can be a wound battery or a stacked battery.

[0131] The positive electrode active material and its application provided by the present invention will be specifically introduced below through specific embodiments.

[0132] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0133] Example 1

[0134] 1) Preparation of composite manganese source

[0135] MnO2 and Mn(OH)2 were mixed in a Mn element molar ratio of 4:6, a certain amount of citric acid (the amount was 30% of the theoretical mass of the composite manganese source) was added, and the mixture was reacted at 85°C for 2h by a sol-gel method to prepare a gel product; the gel product was sintered under N2 protection at a heating rate of 4°C / min, a sintering temperature of 800°C, and a holding time of 6h to obtain the composite manganese source of this embodiment;

[0136] The median particle size D50 of the composite manganese source is 6 μm and the tap density is 3.2 g / cm 2 , with a specific surface area of ​​0.45m 2 / g.

[0137] 2) Preparation of positive electrode active materials

[0138] Li2CO3, the above-mentioned composite manganese source, FePO4, H3PO4, glucose and MgO are mixed, wherein the molar ratio of Li, Mn, Fe and P is 1.02:0.6:0.4:1, the mass of glucose accounts for 10% of the theoretical mass of lithium iron manganese phosphate, and the mass of Mg element accounts for 0.2% of the theoretical mass of lithium iron manganese phosphate; then the above-mentioned mixed system is successively sand-milled and spray-dried to obtain a precursor material; the precursor material is heated to 680°C at a rate of 5°C / min under N2 protection, and the insulation time is 8h to obtain the positive electrode active material of this embodiment.

[0139] Example 2

[0140] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the molar ratio of the Mn element of MnO2 and Mn(OH)2 is 8:2;

[0141] The median particle size D50 of the composite manganese source is 5.5 μm and the tap density is 3.1 g / cm 2 , with a specific surface area of ​​0.47m 2 / g.

[0142] Example 3

[0143] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the molar ratio of the Mn element of MnO2 and Mn(OH)2 is 2:8;

[0144] The median particle size D50 of the composite manganese source is 7 μm and the tap density is 3.4 g / cm 2 , with a specific surface area of ​​0.4m 2 / g.

[0145] Example 4

[0146] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the sintering temperature is 650° C. and the holding time is 6 h.

[0147] Example 5

[0148] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), Mn(OH)2 is replaced by manganese monoxide, manganese tetraoxide and manganese pentoxide (molar ratio is 4:3:3), and the molar ratio of MnO2 to manganese monoxide, manganese tetraoxide and manganese pentoxide is adjusted to 5:5; the heating rate is 2°C / min, the sintering temperature is 700°C, and the sintering time is 3h;

[0149] The median particle size D50 of the composite manganese source is 4.5 μm and the tap density is 2.75 g / cm 2 , with a specific surface area of ​​0.65m 2 / g;

[0150] In step 2), the mass of glucose accounts for 8% of the theoretical mass of lithium manganese iron phosphate, the mass of the doping element accounts for 0.05% of the theoretical mass of lithium manganese iron phosphate, the heating rate is 3°C / min, the sintering temperature is 665°C, and the sintering time is 7h.

[0151] Example 6

[0152] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), Mn(OH)2 is replaced by manganese carbonate, manganese nitrate, and manganese oxalate (molar ratio is 4:3:3), and the molar ratio of MnO2 to manganese carbonate, manganese nitrate, and manganese oxalate is adjusted to 6:4; the heating rate is 3°C / min, the sintering temperature is 750°C, and the sintering time is 5h;

[0153] The median particle size D50 of the composite manganese source is 5 μm and the tap density is 3 g / cm 2 , with a specific surface area of ​​0.5m 2 / g;

[0154] In step 2), the mass of glucose accounts for 9% of the theoretical mass of lithium manganese iron phosphate, the mass of the doping element accounts for 0.25% of the theoretical mass of lithium manganese iron phosphate, the heating rate is 7°C / min, the sintering temperature is 690°C, and the sintering time is 9h.

[0155] Example 7

[0156] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), Mn(OH)2 is replaced by manganese dihydrogen phosphate, manganese nitrate and manganese acetate (molar ratio is 4:3:3), and the molar ratio of MnO2 to manganese dihydrogen phosphate, manganese nitrate and manganese acetate is adjusted to 7:3; the heating rate is 5°C / min, the sintering temperature is 900°C, and the sintering time is 8h;

[0157] The median particle size D50 of the composite manganese source is 8.2 μm and the tap density is 3.5 g / cm 2 , with a specific surface area of ​​0.35m 2 / g;

[0158] In step 2), the mass of glucose accounts for 12% of the theoretical mass of lithium iron manganese phosphate, the mass of the doping element accounts for 0.5% of the theoretical mass of lithium iron manganese phosphate, the heating rate is 8°C / min, the sintering temperature is 700°C, and the sintering time is 10h.

[0159] Example 8

[0160] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the mass of glucose accounts for 13% of the theoretical mass of lithium manganese iron phosphate.

[0161] Example 9

[0162] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), the sintering temperature is 700° C. and the sintering time is 3 h;

[0163] The median particle size D50 of the composite manganese source is 4 μm, and the tap density is 2.5 g / cm 2 , with a specific surface area of ​​0.70m 2 / g;

[0164] In step 2), the sintering temperature is 650°C and the sintering time is 6 hours.

[0165] Example 10

[0166] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), the molar ratio of MnO2 to Mn(OH)2 is 2:8; the heating rate is 5°C / min, the sintering temperature is 900°C, and the sintering time is 8h;

[0167] The median particle size D50 of the composite manganese source is 9 μm and the tap density is 3.8 g / cm 2 , with a specific surface area of ​​0.3m 2 / g;

[0168] In step 2), the sintering temperature is 700°C and the sintering time is 6 hours.

[0169] Embodiment 11

[0170] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), the molar ratio of MnO2 to Mn(OH)2 is 8:2; the sintering temperature is 700°C, and the sintering time is 3h;

[0171] The median particle size D50 of the composite manganese source is 4 μm, and the tap density is 2.5 g / cm 2 , with a specific surface area of ​​0.7m 2 / g;

[0172] In step 2), the mass of glucose accounts for 8% of the theoretical mass of lithium manganese iron phosphate, the heating rate is 8°C / min, the sintering temperature is 650°C, and the sintering time is 6h.

[0173] Example 12

[0174] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the positive electrode active material is not doped with Mg element.

[0175] Example 13

[0176] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the mass of the Mg element accounts for 0.6% of the theoretical mass of lithium manganese iron phosphate.

[0177] Comparative Example 1

[0178] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 1), the molar ratio of the Mn element of MnO2 and Mn(OH)2 is 9:1.

[0179] Comparative Example 2

[0180] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 2), the sintering temperature is 720° C. and the holding time is 12 h.

[0181] Comparative Example 3

[0182] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 1), only MnO2 and citric acid are subjected to a sol-gel reaction under unchanged reaction conditions, and then sintered under unchanged sintering conditions to obtain the manganese source of this comparative example;

[0183] The median particle size D50 of the manganese source is 2 μm and the tap density is 2.1 g / cm 2 , with a specific surface area of ​​0.9m 2 / g.

[0184] Comparative Example 4

[0185] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 2), conventional manganese sources MnO2 and Mn(OH)2 are used without any treatment.

[0186] Comparative Example 5

[0187] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 1), the sintering temperature is 650° C. and the holding time is 9 h.

[0188] Test example

[0189] 1. The physical and chemical properties of the positive electrode active materials prepared in the above examples and comparative examples are characterized, including the following steps. The characterization results are shown in Tables 1 and 2.

[0190] 1) SEM test

[0191] The SEM image is obtained by performing SEM testing on the positive electrode active material; the size of the primary particles in the SEM image is calibrated and counted using the professional particle size analysis software NanoMeasurer to obtain the particle size range, D10, D50, D90, and the number of primary particles A and primary particles B. The ratio of the number of primary particles A to primary particles B and the discreteness of the particle size distribution of the primary particles can be obtained by calculation.

[0192] Figure 1 is a SEM image of the composite manganese source prepared in Example 1, Figure 2 This is a SEM image of the positive electrode active material prepared in Example 1.

[0193] 2) XRD test

[0194] The positive electrode active material was subjected to XRD test, and the original data was refined and fitted using XRD analysis software to obtain the mass content of lithium manganese oxide in the positive electrode active material.

[0195] Figure 3 is the XRD pattern of the positive electrode active material in Example 1, Figure 3 It can be seen that the above-mentioned positive electrode active material has the characteristic crystal phase structure of lithium iron manganese phosphate and lithium manganate at the same time, which means that the positive electrode active material includes a solid solution formed by lithium iron manganese phosphate and lithium manganate.

[0196] 3) ICP test

[0197] The positive electrode active material is subjected to ICP testing to obtain the mass content of the doping element in the positive electrode active material.

[0198] 4) Porosity

[0199] The gas adsorption method (BET method) is used to measure the gas adsorption amount of the positive electrode active material under different pressures, and the porosity is calculated.

[0200] 5) Powder compaction density

[0201] The positive electrode active material was tested using a powder compaction density instrument with a test pressure of 220 MPa and a pressure holding time of 15 s.

[0202] 6) Carbon and sulfur analysis test

[0203] The positive electrode active material is tested using a carbon-sulfur analyzer to obtain the mass content of the carbon coating layer in the positive electrode active material.

[0204] Table 1

[0205]

[0206] Table 2

[0207]

[0208] 2. The positive electrode active materials prepared in the above embodiments and comparative examples are made into button batteries, comprising the following steps:

[0209] At 25°C and normal pressure (0.1MPa), positive electrode active material, conductive carbon black and binder polyvinylidene fluoride (PVDF) with a mass percentage ratio of 95:3:2 were added to N-methylpyrrolidone solvent, and the mixture was stirred and mixed to obtain positive electrode active slurry; the positive electrode active slurry was coated on the surface of aluminum foil, and the positive electrode sheet was obtained after drying and cold pressing, wherein the thickness of the positive electrode active layer was 100μm and the surface density was 1.4g / cm 2 , compacted density is 2.2g / cm 3; The positive electrode sheet is then punched out with a film mold to obtain a small disc with a diameter of 12 mm. After drying and weighing, a button battery is assembled together with an electrolyte in a glove box under an Ar protective atmosphere using a 2025 button battery shell, a Li metal disc as the negative electrode, and polyethylene (PE) as a separator; wherein the electrolyte includes a lithium salt and an organic solvent, the lithium salt is lithium hexafluorophosphate (LiPF6) with a concentration of 1 mol / L, and the solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1.

[0210] The electrochemical performance of the battery prepared above was tested:

[0211] 1) First Coulomb efficiency

[0212] The batteries were charged at a constant current of 0.1C to 4.5V, and then charged at a constant voltage of 4.5V to a current of 0.05C. The charging capacity at this time was recorded as the first cycle charging capacity. After that, the batteries were allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.5V. The batteries were cycled 5 times according to the above-mentioned charging and discharging mechanism, and the discharge capacity after the cycle was recorded. The first coulombic efficiency (%) = (discharge capacity after the cycle / first cycle charging capacity) × 100%.

[0213] 2) Lithium ion migration rate

[0214] Lithium ion migration rate of positive electrode active material (cm 2 / s) is obtained by cyclic voltammetry test combined with powder impedance test fitting, and is specifically calculated by formula 2:

[0215] Formula 2

[0216] In formula 2, Indicates the lithium ion migration rate of the positive electrode active material;

[0217] R represents the gas constant, R≈8.314, unit J·(mol·K) -1 ;

[0218] T represents absolute temperature, T=273.15+actual temperature (℃), K;

[0219] A is the surface area of ​​the electrode, cm 2 ;

[0220] n represents the number of electrons gained or lost per mole of molecules involved in the redox reaction;

[0221] F represents the Faraday constant, which is 69485.3 C·mol -1 ;

[0222] Represents Li+ Concentration, about 0.059 mol·L -1 ;

[0223] σ represents the Warburg factor;

[0224] Among them, R, T, A, n, F, Obtained through cyclic voltammetry test; σ is the slope of the low-frequency straight line obtained by impedance spectrum analysis fitting.

[0225] The test results are shown in Table 3.

[0226] 3. The positive electrode active materials prepared in the above embodiments and comparative examples are made into a full battery, comprising the following steps:

[0227] The positive electrode active materials in the above embodiments and comparative examples were prepared into positive electrode active slurry, the slurry formula was consistent with the formula in the button battery, the positive electrode active slurry was coated on both surfaces of the aluminum foil, and the positive electrode sheet was obtained after drying and cold pressing, wherein the total thickness of the positive electrode active layer was 100 μm, and the double-sided surface density was 1.4 g / cm 2 , double-sided compaction density is 2.2g / cm 3 ; The negative electrode is made of graphite, and the diaphragm and electrolyte are consistent with those in the buckle battery; the aforementioned positive electrode sheet, diaphragm, and negative sheet are stacked in order, so that the isolation membrane is between the positive and negative electrode sheets to play an isolating role, and then wound into a square bare battery cell, loaded with aluminum-plastic film, and after baking to remove water, the above-mentioned electrolyte is injected and sealed, and after standing, hot and cold pressing, formation, clamping, capacity division and other processes, a full battery is obtained.

[0228] 1) Cycle performance

[0229] The above full battery is charged at 25°C at a constant current of 1C to 4.5V, then charged at a constant voltage of 0.5C to 4.5V, and then discharged at a discharge rate of 1C to 2.5V, and the initial discharge capacity is recorded as Q1; cycle 500 times according to the above-mentioned charge and discharge mechanism, and the discharge capacity after the cycle is recorded as Q2; the cycle capacity retention rate (%) = (Q2 / Q1) × 100%.

[0230] 2) Energy density

[0231] The mass of the positive electrode active material loaded per unit area of ​​the positive electrode sheet in the above-mentioned full battery is measured respectively, which is M; at room temperature 25°C, the full battery is charged to a voltage of 4.5V at a rate of 0.33C, and then discharged to a voltage of 2.5V at a rate of 0.33C, and the discharge energy S is measured; then the energy density (Wh / kg) = S / M.

[0232] The test results are shown in Table 3.

[0233] Table 3

[0234]

[0235] From Table 1 to Table 3, we can see that:

[0236] Compared with Comparative Examples 1 to 5, Examples 1 to 13 have higher electrochemical performance and energy density. In particular, the lithium ion migration efficiency of the positive electrode active material in Example 1 is relatively high, which is 3.0×10 -12 cm 2 / s, and accordingly, the discharge capacity of the battery including the positive electrode active material at 0.1C is 158.1 mAh·g -1 The first coulombic efficiency is 98.5%, the 500-cycle capacity retention rate is 98.0%, and the energy density is 220Wh / kg, which is significantly higher than the performance of the positive electrode active material and the battery in the comparative example. It can be seen that the positive electrode active material in the present invention can significantly improve the electrochemical performance (capacity, first coulombic efficiency and cycle performance) and energy density of the battery.

[0237] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes secondary particles composed of primary particles; the primary particles include an inner core and a carbon coating layer disposed on at least a portion of the surface of the inner core; the inner core includes a solid solution formed by lithium manganese iron phosphate and lithium manganate; The primary particles include primary particles A and primary particles B. The particle size of the primary particles A is 50 to 200 nm, and the median particle size D50 is 80 to 120 nm. The particle size of the primary particles B is 400 to 800 nm, and the median particle size D50 is 500 to 600 nm.

2. The positive electrode active material according to claim 1, characterized in that The mass content m of the lithium manganate in the positive electrode active material satisfies 0<m≤3%; And / or, the mass content z of the carbon coating layer in the positive electrode active material satisfies 0<z≤3%.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The ratio of the number of the primary particles A to the number of the primary particles B is 2:8 to 8:2; and / or, the porosity of the secondary particles is 5 to 25%; And / or, the particle size distribution dispersion of the primary particles is 1.67 to 2.

86.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The powder compaction density of the positive electrode active material is 2.26-2.46 g / cm 3 .

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode active material also includes a doping element; The doping element includes at least one of Al, Mg, Ni, Co, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y; Preferably, the mass content of the doping element in the positive electrode active material is 500 to 5000 ppm.

6. The positive electrode active material according to claim 5, characterized in that The chemical composition of the solid solution satisfies Formula 1, Li 1+b Fe 1-x-y Mn x D y PO4·LiMn2O4 Formula 1 In Formula 1, -0.01≤b≤0.04, 0.2≤x≤0.8, 0.0005≤y≤0.005, and D is the doping element.

7. A method for preparing a positive electrode active material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing MnO2 and a manganese-containing compound with a complexing agent in a molar ratio of (0.2-0.8): (0.8-0.2), reacting at 80-100° C. for 1-3 hours to obtain a gel product; sintering the gel product at 700-900° C. for 3-8 hours in an inert atmosphere to obtain a composite manganese source; The raw material system including the lithium source, the composite manganese source, the iron source, the phosphorus source and the carbon source is sequentially subjected to sand milling and spray drying to obtain a precursor material; the precursor material is heat-sintered at 650-700° C. for 6-10 hours to obtain the positive electrode active material.

8. The method for preparing a positive electrode active material according to claim 7, characterized in that: The median particle size D50 of the composite manganese source is 4 to 9 μm, and / or the tap density is 2.50 to 3.80 g / cm 2 , and / or, specific surface area of ​​0.30 to 0.70 m 2 / g.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 6, or the positive electrode active material prepared by the preparation method according to claim 7 or 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode active material according to any one of claims 1 to 6, or the positive electrode active material prepared by the preparation method according to claim 7 or 8, or the positive electrode sheet according to claim 9.

Citation Information

Cited By

  • Lithium ion secondary battery, battery device, power utilization device, preparation method of positive active material and preparation method of positive pole piece

    CN120072865A

  • Lithium-ion secondary battery, battery apparatus, electrical apparatus, preparation method for positive electrode active material, and preparation method for positive electrode plate

    US12706303B1

  • Positive electrode active material, positive electrode sheet, battery, and electric device

    WO2026153283A1